Tetrathiafulvalene-based azine ligands for anion and metal cation coordination - Ayadi, Awatef; El Alamy, Aziz; Alévêque, Olivier; Allain, Magali; Zouari, Nabil; Bouachrine, Mohammed; El-Ghayoury, Abdelkrim (Beilstein Journal of Organic Chemistry, 2015)
The synthesis and full characterization of two tetrathiafulvalene-appended azine ligands, namely 2-([2,2’-bi(1,3-dithiolylidene)]-4-yl)-6-((2,4-dinitrophenyl)hydrazono)methyl)pyridine (L1) and 5-([2,2’-bi(1,3-dithiolylidene)]-4-yl)-2-((2,4-dinitrophenyl)hydrazono)methyl)pyridine (L2) are described. The crystal structure of ligand L1 indicates that the ligand is completely planar with the presence of a strong intramolecular N3–H3···O1 hydrogen bonding. Titration experiments with inorganic anions showed that both ligands are suitable candidates for the sensing of fluoride anions. Ligand L2 was reacted with a Re(I) cation to yield the corresponding rhenium tricarbonyl complex 3. In the crystal structure of the newly prepared electroactive rhenium complex the TTF is neutral and the rhenium cation is hexacoordinated. The electrochemical behavior of the three compounds indicates that they are promising for the construction of crystalline radical cation salts.
Keywords: azine ligand; fluoride sensing; rhenium; tetrathiafulvalene; X-ray

(untitled) - Bendikov, M.; Wudl, F.; Perepichka, D. F. (Chem. Rev., 2004)

(untitled) - Wudl, F.; Wobschall, D.; Hufnagem, E. J. (J. Am. Chem. Soc., 1972)

(untitled) - Ferraris, J.; Cowan, D. O.; Walatka, V.; Perlstein, J. H. (J. Am. Chem. Soc., 1973)

Molecular conductors (Chem. Rev., 2004)

(untitled) - Martín, N. (Chem. Commun., 2013)

Organic Superconductors (Including fullerenes), Synthesis, Structure, properties and Theory - Williams, J. M.; Ferraro, J. R.; Thorn, R. J.; Carlson, K. D.; Geiser, U.; Wang, H. H.; Kini, A. M.; Whangbo, M.-H. (Prentice Hall, 1992)

(untitled) - Bryce, M. R.; Murphy, L. C. (Nature, 1984)

(untitled) - McCall, K. L.; Morandeira, A.; Durrant, J.; Yellowlees, L. J.; Robertson, N. (Dalton Trans., 2010)

(untitled) - Wenger, S.; Bouit, P.-A.; Chen, Q. L.; Teuscher, J.; Di Censo, D.; Humphry-Baker, R.; Moser, J.-E.; Delgado, J. L.; Martín, N.; Zakeeruddin, S. M.; Grätzel, M. (J. Am. Chem. Soc., 2010)

(untitled) - de Lucas, A. I.; Martín, N.; Sánchez, L.; Seoane, C.; Andreu, R.; Garín, J.; Orduna, J.; Alcalá, R.; Villacampa, B. (Tetrahedron, 1998)

(untitled) - González, M.; Segura, J. L.; Seoane, C.; Martín, N.; Garín, J.; Orduna, Jesús; Alcalá, R.; Villacampa, B.; Hernández, V.; López Navarrete, J. T. (J. Org. Chem., 2001)

(untitled) - Ouahab, L. (Chem. Mater., 1997)

(untitled) - Coronado, E.; Galán-Marcós, J. R.; Gómez-García, C. J.; Laukhin, V. (Nature, 2000)

(untitled) - Ouahab, L.; Enoki, T. (Eur. J. Inorg. Chem., 2004)

(untitled) - Coronado, E.; Day, P. (Chem. Rev., 2004)

(untitled) - Setifi, F.; Ouahab, L.; Golhen, S.; Yoshida, Y.; Saito, G. (Inorg. Chem., 2003)

(untitled) - Nihei, M.; Takahashi, N.; Nishikawa, H.; Oshio, H. (Dalton Trans., 2011)

(untitled) - Canevet, D.; Sallé, M.; Zhang, G.; Zhang, D.; Zhu, D. (Chem. Commun., 2009)

(untitled) - Nielsen, M. B.; Lomholt, C.; Becher, J. (Chem. Soc. Rev., 2000)

(untitled) - Segura, J. L.; Martín, N. (Angew. Chem., Int. Ed., 2001)

TTF Chemistry: Fundamentals & Applications of Tetrathiafulvalene - Yamada, J.; Sugimoto, T. (Kodansha and Springer, 2004)

(untitled) - Hardouin-Lerouge, M.; Hudhomme, P.; Sallé, M. (Chem. Soc. Rev., 2011)

Supramolecular Chemistry: Concepts and Perspectives - Lehn, J. M. (Chapter 3, 1995)

Supramolecular Chemistry of Anions - Bianchi, E.; Bowman-James, K.; García-España, E. (Wiley-VCH, 1997)

(untitled) - Schmidtchen, F. P.; Berger, M. (Chem. Rev., 1997)

(untitled) - Beer, P. D. (Acc. Chem. Res., 1998)

(untitled) - Bowman-James, K. (Acc. Chem. Res., 2005)

Anion Receptor Chemistry - Sessler, J. L.; Gale, P. A.; Cho, W. S. (Royal Society of Chemistry, 2006)

(untitled) - Caltagirone, C.; Gale, P. A. (Chem. Soc. Rev., 2009)

(untitled) - Gale, P. A.; García-Garrido, S. E.; Garric, J. (Chem. Soc. Rev., 2008)

(untitled) - Suksai, C.; Tuntulani, T. (Chem. Soc. Rev., 2003)

Biochemistry of the Halogens and Inorganic Halides - Kirk, K. L. (Springer, 1991)

(untitled) - Hudnall, T. W.; Chiu, C.-W.; Gabbaï, F. P. (Acc. Chem. Res., 2009)

(untitled) - Lee, C.-H.; Miyaji, H.; Yoon, D.-W.; Sessler, J. L. (Chem. Commun., 2008)

(untitled) - Belhadj, E.; El-Ghayoury, A.; Cauchy, T.; Allain, M.; Mazari, M.; Sallé, M. (Eur. J. Inorg. Chem., 2014)
And references therein.

(untitled) - Xiong, J.; Cui, L.; Liu, W.; Beves, J. E.; Li, Y.-Y.; Zuo, J.-L. (Tetrahedron Lett., 2013)
And references therein.

(untitled) - Shi, Z.; Han, Q.-H.; Li, X.-Y.; Shao, M.-Y.; Zhu, Q.-Y.; Dai, J. (Dalton Trans., 2011)

(untitled) - Chahma, M.; Wang, X. S.; van der Est, A.; Pilkington, M. (J. Org. Chem., 2006)

(untitled) - Yu, M.; Fan, Z.; Jing, Z.-L.; Chen, X.; Diao, C.-H.; Deng, Q.-L. (Acta Crystallogr., 2005)

Gaussian03, Revision B.04 (Gaussian, Inc., 2003)

(untitled) - Zhou, L.; Zhang, X.; Wu, S. (Chem. Lett., 2004)

(untitled) - Chawla, H. M.; Sahu, S. N.; Shrivastava, R.; Kumar, S. (Tetrahedron Lett., 2012)

(untitled) - Sun, Y.; Liu, Y.; Guo, W. (Sens. Actuators, B, 2009)

(untitled) - Li, J.; Lin, H.; Cai, Z.; Lin, H. (Spectrochim. Acta, Part A, 2009)

(untitled) - Upadhyay, K. K.; Mishra, R. K.; Kumar, V.; Chowdhury, P. K. R. (Talanta, 2010)

(untitled) - Amendola, V.; Esteban-Gómez, D.; Fabbrizzi, L.; Licchelli, M. (Acc. Chem. Res., 2006)

(untitled) - Jia, H.-P.; Forgie, J. C.; Liu, S.-X.; Sanguinet, L.; Levillain, E.; Le Derf, F.; Sallé, M.; Neels, A.; Skabara, P. J.; Decurtins, S. (Tetrahedron, 2012)

(untitled) - Singh, A.; Chandra, M.; Sahay, A. N.; Pandey, D. S.; Pandey, K. K.; Mobin, S. M.; Carmen Puerta, M.; Valerga, P. (J. Organomet. Chem., 2004)

(untitled) - Sarjit Singh, K.; Mozharivskyj, Y. A.; Thöne, C.; Rao Kollipara, M. (J. Organomet. Chem., 2005)

(untitled) - Liu, W.; Heinze, K. (Dalton Trans., 2010)

(untitled) - El-Ghayoury, A.; Leliège, A.; Allain, M.; Batail, P. (Tetrahedron Lett., 2013)